2009
DOI: 10.1634/theoncologist.2008-0193
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Approaches for Infants with Malignant Central Nervous System Tumors

Abstract: DisclosuresLucie Lafay-Cousin: None; Douglas Strother: None.Section editors Susan M. Blaney and Ross Pinkerton have disclosed no financial relationships relevant to the content of this article.The content of this article has been reviewed by independent peer reviewers to ensure that it is balanced, objective, and free from commercial bias. LEARNING OBJECTIVES1. Evaluate the challenges of identifying very young children with brain tumors so that they can be enrolled in clinical trials.2. Identify prognostic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 110 publications
0
44
0
6
Order By: Relevance
“…6 On the other hand, brain tumors in infants and young children are frequently large and highly vascular, and complete resection is often difficult due to the risks of neurological complications and excessive blood loss. Relatively small circulating blood volume in infants and young children lowers the threshold of tolerance for intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 On the other hand, brain tumors in infants and young children are frequently large and highly vascular, and complete resection is often difficult due to the risks of neurological complications and excessive blood loss. Relatively small circulating blood volume in infants and young children lowers the threshold of tolerance for intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…While more extensive resection has been demonstrated to correlate with improved outcomes in most brain tumors in infants and young children, complete resection is often challenging due to the risks of neurological complications and excessive blood loss. 2,4,6 In such cases, neoadjuvant chemotherapy may reduce the size and/or the vascularity of the tumor, facilitate maximal tumor resection, and contribute to improving outcomes. 5,9 We retrospectively analyzed the intraoperative blood loss, extent of resection, neurological complications, and outcomes after secondlook surgery following neoadjuvant chemotherapy in 9 patients with brain tumors.…”
mentioning
confidence: 99%
“…Not surprisingly, the results are extremely variable in the absence of a standard protocol and superiority of one treatment modality over another. Strategies like ‘HTT-SKK' (use of high-dose systemic methotrexate with intraventricular methotrexate), high-dose myeloablative chemotherapy with autologous stem cell rescue, low-dose radiation with a tumor bed boost, or use of conformal RT have been employed to avoid the adverse effects of conventional RT [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on current literature, however, it is clearly shown that cytoreductive surgery with neoadjuvant chemotherapy and stem cell support produces some of the best outcomes in the treatment of intracranial pediatric malignancies. 7,14 Recent reports have confirmed the utility of gross-total resection of pediatric tumors subsequent to chemotherapy. 24 In this situation, it is not clear what the implications would have been if the errant tumor was left in the ventricle.…”
Section: 13mentioning
confidence: 95%